2014
DOI: 10.1096/fj.14-264036
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin/apolipoprotein J binds to aggregated LDL in human plasma and plays a protective role against LDL aggregation

Abstract: Clusterin/apolipoprotein J (apoJ) is an extracellular chaperone involved in the quality control system against protein aggregation. A minor part of apoJ is transported in blood bound to LDLs, but its function is unknown. Our aim was to determine the role of apoJ bound to LDLs. Total LDL from human plasma was fractionated into native LDL [LDL(+)] and electronegative LDL [LDL(-)]. The latter was separated into nonaggregated [nagLDL(-)] and aggregated LDL(-) [agLDL(-)]. The content of apoJ was 6-fold higher in LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 51 publications
1
29
1
Order By: Relevance
“…1–3). This observation agrees with previous reports that LDL(−) has increased susceptibility to aggregation upon other perturbations, such as intense agitation, prolonged incubation at 37 °C, or phospholipase treatment [17,18,27,29,38,46]. Our TEM and NGGE data confirm the presence of aggregated particles in LDL(−) isolated from blood.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…1–3). This observation agrees with previous reports that LDL(−) has increased susceptibility to aggregation upon other perturbations, such as intense agitation, prolonged incubation at 37 °C, or phospholipase treatment [17,18,27,29,38,46]. Our TEM and NGGE data confirm the presence of aggregated particles in LDL(−) isolated from blood.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, apoJ and apoA-I are known to prevent LDL aggregation, fusion and rupture [21,22]. Western blot analysis confirmed increased apoA-I and apoJ content in LDL(−) compared to LDL(total) or LDL(+) and showed that endogenous apoJ remained intact after 15 min of incubation at 82 °C, while endogenous apoA-I was largely intact even after 90 min (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The function of apoJ in LDL is unclear, but it has been suggested that could inhibit LDL-mediated cytotoxicity [25]. More recently, we have reported that apoJ could play a protective role preventing LDL from aggregation [26].…”
Section: Introductionmentioning
confidence: 94%